TRAINING OF A TEACHER OF NATURAL DISCIPLINES IN CONTEXTS OF THE DEVELOPMENT OF MODERN EDUCATION (Pedagogy of Higher and Secondary Education, 2008)
The author of the article considers the issues of prospects of further development of the system of higher professional training of physics teachers. It has been stated that the process of education modernisation pre-supposes the development of the newest programme-methodical provision for the process of training.